Social Reality Construction of Muhammadiyah Citizens in Respect of LAZISMU during the Covid-19 Pandemic - Radhiyatul Fithri; Baidarus Baidarus (Cakrawala: Jurnal Studi Islam, 2021)
For the Indonesian people, LAZISMU, as an Islamic philanthropic institution, shapes the cultural character of zakat, infaq, and alms. Furthermore, following the outbreak of the covid-19 pandemic, the Muhammadiyah encouraged LAZISMU with raising funds for the program under the slogan "Together Against the Corona Virus." LAZISMU Riau and Pekanbaru city continue to strive to become professional zakat institutions with good governance as a place for distributing charity funds to the public and Persyarikatan members in particular. Muhammadiyah citizens' attitudes toward these two LAZISMUs, on the other hand, are not directly proportional to their engagement in LAZISMU's programs. Muhammadiyah citizens, in particular, believe that LAZISMU Pekanbaru City is a professional Amil Zakat Institution with good governance. The construction of this social reality, however, has not been able to increase their participation in tithing to LAZISMU. This is not the same case with LAZISMU Riau, which was known as an institution with poor governance. However, the ideological aspect is a factor that encourages Muhammadiyah citizens to participate in the LAZISMU program.